Rapid low-resource detection of Plasmodium falciparum in infected Anopheles mosquitoes - Hugo, Leon E.; van Huyssteen, Karla; Oloniniyi, Olamide; Donnelly, Laura; Conn, Anna; Collins, Katharine A.; Mitchell, Hayley; McCarthy, James S.; Macdonald, Joanne (Frontiers in Tropical Diseases, 2024)
Vector surveillance of Plasmodium falciparum is critical for monitoring and reducing one of the most severe forms of malaria, which causes high morbidity and mortality in children under five and pregnant women. Here we developed a rapid and highly sensitive test for the detection of P. falciparum (Pf)-infected mosquitoes (Rapid Pf test), with high suitability for low-resource vector surveillance implementation. The Rapid Pf test had similar analytical sensitivity to laboratory-based tests, detecting down to 4 copies/μL of a 18S rRNA DNA standard. In addition, the Rapid Pf test could be completed in less than 30 minutes, and only required a liquid sample preparation reagent, pestle, tube, and 39°C heating block for operation, indicating amenability for low-resource implementation. Diagnostic testing was performed using Anopheles stephensi mosquitoes, either uninfected, or fed with P. falciparum gametocyte cultures. These P. falciparum fed mosquitoes were determined to have 79% infection prevalence based on parallel microscopy and qPCR testing on a subset of 19 mosquitoes. However, our Rapid Pf test determined a 90% positive test rate when testing individual infected mosquitoes (n=30), and did not detect 40 uninfected mosquitoes regardless of blood-fed status (n=40), suggesting the true prevalence of infection in the mosquitoes may have been higher than calculated by qPCR and microscopy. The Rapid Pf test was demonstrated to detect infection in individual mosquitoes (both fresh and frozen/thawed), as well as pools of 1 infected mosquito mixed with 19 known uninfected mosquitoes, and individual mosquitoes left in traps for up to 8 days. After testing on infected and uninfected mosquitoes (n=148) the Rapid Pf test was conservatively estimated to achieve 100% diagnostic sensitivity (95% confidence interval, CI: 91%-100%) and 97% diagnostic specificity (CI: 92%-99%) compared to the estimated prevalence from combined microscopy and qPCR results. These results indicate the Rapid Pf test could provide a highly effective tool for weekly surveillance of infected mosquitoes, to assist with P. falciparum monitoring and intervention studies.